2000
DOI: 10.1677/joe.0.1670391
|View full text |Cite
|
Sign up to set email alerts
|

The Dstpk61 locus of Drosophila produces multiple transcripts and protein isoforms, suggesting it is involved in multiple signalling pathways

Abstract: The Drosophila gene Dstpk61 encodes a serine threonine protein kinase homologous to human phosphoinositidedependent protein kinase (PDK1), and also has homologues in S. cerevisiae, S. pombe, C. elegans, A. thaliana, mouse, and sheep. Where its function has been investigated, this kinase is thought to be involved in regulating cell growth and survival in response to extracellular signals such as insulin and growth factors. In Drosophila it produces multiple transcripts, some of which appear to be sex-specific.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…This finding suggests that PDK-1 may be a cytoplasmic-nuclear-shuttling protein. Consistent with this hypothesis, it has been reported that Drosophila PDK-1 possesses a putative bipartite nuclear localization signal (16) that is also conserved in the mouse and human protein. To examine whether PDK-1 undergoes nuclear translocation, we treated CHO͞IR cells expressing Myc-mPDK-1 with leptomycin B (LMB), a specific inhibitor of CRM1-mediated nuclear export (21,22).…”
Section: Pdk-1 Is a Cytoplasmic-nuclear-shuttling Protein And Contains Asupporting
confidence: 54%
See 1 more Smart Citation
“…This finding suggests that PDK-1 may be a cytoplasmic-nuclear-shuttling protein. Consistent with this hypothesis, it has been reported that Drosophila PDK-1 possesses a putative bipartite nuclear localization signal (16) that is also conserved in the mouse and human protein. To examine whether PDK-1 undergoes nuclear translocation, we treated CHO͞IR cells expressing Myc-mPDK-1 with leptomycin B (LMB), a specific inhibitor of CRM1-mediated nuclear export (21,22).…”
Section: Pdk-1 Is a Cytoplasmic-nuclear-shuttling Protein And Contains Asupporting
confidence: 54%
“…These observations suggest that an intact PI3-kinase pathway may be reconstituted in the nucleus to regulate nuclear events such as gene transcription. Sequence analysis of Drosophila PDK-1 Dstpk61 revealed the presence of a putative bipartite nuclear localization signal (16). In this study, we demonstrate that PDK-1 is a cytoplasmic-nuclear-shuttling protein.…”
mentioning
confidence: 54%
“…In Drosophila, the DSTPK61 gene produces multiple transcripts that encode for at least four different protein isoforms with variant N-termini [44,45]. Analysis of PDK1 cDNAs isolated from human [37], rat [20] and mouse [25] suggests that mammalian pdk1 may similarly give rise to alternatively spliced transcripts.…”
Section: Cloning and Characterization Of Pdk1mentioning
confidence: 99%